Does GATS’ influence on private university sector’s growth ensure ESD or develop city ‘sustainability crisis’—policy framework to respond COP21 - Alam, Gazi Mahabubul; Roslan, Samsilah; Al-Amin, Abul Quasem; Filho, Walter Leal (Multidisciplinary Digital Publishing Institute, 2021)
The conventions and ratifications made by the United Nations (UN) have a long history. They were well respected for their ability to unite the world’s countries on some issues. The paradigm transformation of UN ratifications to combine both business models and social justice has received both positive and negative responses. While adherents argue that such a transformation is fundamental to boost economic development, opponents assert that the ‘so-called paradigm transformation’ has benefited the West by victimising the East, which has essentially complicated the global ‘sustainability crisis’. This also hinders executing the ESD (education for sustainable development) concept, especially in developing countries. The concept of ‘sustainable development’ is now the main agenda item of UN conventions. COP21 (United Nations Climate Change Conference in 2015, otherwise known as the 21st Conference of the Parties), is an example of the UN’s seriousness in addressing the ‘global sustainability crisis’. GATT and GATS are the international policies that are, respectively, the ‘causer’ and ‘developer’ of the private university sector in emerging market economies. Critics claim that this expanding sector generates an urban sustainability crisis. This study examined the effect of private universities’ expansion on urban sustainability, using a qualitative method for assessing primary and secondary data. The indices for night light intensity, heat and greenery served as the essential parameters to calculate the sustainability crisis. Results indicate that while the greenery index has fallen significantly, night light and heat indices have unexpectedly increased, which correlate with the development and expansion of the private university sector. To respond to COP21, a ‘carbon neutrality’ policy framework for the sector is suggested in an effort to control the sustainability crisis.